Developing a metadata elements set for digital archives of Chinese restoration techniques: A scoping literature review - Yue, Ming; Me, Rosalam Che; Yimin, Li; Rahmat, Rahmita Wirza O. K. (Multidisciplinary Reviews, 2025)
Metadata elements sets are widely used to describe the information resources comprising digital archives of tangible and intangible cultural heritage. Chinese restoration techniques are precious traditional craftsmanship, which have received much attention on practical protection instead of the information resource management. The list of Chinese intangible cultural heritage includes five restoration categories, including bronzes, ancient clocks, ancient buildings, and ancient ceramics. However, research on metadata related to information resources management remains limited. This study aims to review information regarding metadata descriptions utilized in digital archives for traditional craftsmanship and formulate a set of metadata elements for ancient restoration techniques.  A scoping review was conducted, encompassing 440 peer-reviewed articles from four databases (Scopus, ScienceDirect, CNKI, and IEEE Xplore), along with 61 policy documents, occupational standards, and implemented cases retrieved from key websites (e.g., official organizations and digital archives and digital libraries). The frequencies of each craftsmanship’s core metadata element among the screened thirty-five studies have been analyzed from the perspective of Institutional Metadata and Non-institutional metadata. We survey a method for developing a metadata elements set for digital archives of ancient restoration techniques based on the Dublin Core Element Set (DC) and the Adoption and Documentation Standard of Traditional Craftsmanship of Chinese ICH (ADSTC-CICH). And developed a metadata elements set for Chinese restoration techniques with this method. Then map the scope, challenges, and practices of these initiatives. Future research can either  focus on the metadata elements set developing method or apply this metadata elements set to other types of craftsmanship to promote the safeguarding of intangible cultural heritage.